Ecology of Forest Ecosytem: Inventory of Macroscopic Mushrooms in Taman Hutan Raya Bukit Barisan Area, Karo Regency, North Sumatra Province - Zul Ilmi Hasibuan; Kartika Manalu; Efrida Pima Sari Tambunan (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2021)
Introduction: The research was aimed to identify the types of macroscopic mushrooms and habit characteristics of macroscopic mushrooms in Taman Hutan Raya Bukit Barisan Karo Regency North Sumatra. Materials and Methods: The research was conducted in Taman Hutan Raya Bukit Barisan, Karo Regency, North Sumatra from August until October 2019. The research method used in sampling was the Exploration Method. Results: showed 23 species of macroscopic mushrooms. The highest family is Ganodermatacea with 4 species and the lowest family is Strophariaceae, Hydnangiaceae, Mycenaceae, Fomitopsidaceae, Crepidateceae, Agariceae, Inocybaceae, Russulaceae, Streaceae, and Tricholomateceae with 1 species. Habitat characteristics that are mostly found in weathered wood are found in 13 types of fungi, and at least found in live wood, only 1 species of macroscopic fungi are found.